Marketing Mix of Mban Man White Tofu Factory - Sri Amelia; Ersis Warmansyah Abbas; Raihanah Sari; Rusmaniah Rusmaniah; Jumriani Jumriani (Journal of Social Development, 2026)
Mbah Man's White Tofu Factory is a micro-business that employs traditional yet consistent marketing strategies. This study aims to analyze the implementation of the marketing mix, which includes product, price, place, and promotion aspects, as applied by Mbah Man's White Tofu Factory in Gang Pangeran Suryanata, Banjarmasin. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The informants in this study consist of the factory owner, production manager, employees, and distributors. The results of the study indicate that: The product aspect shows that the factory maintains consistent tofu quality with a soft, dense texture that does not easily crumble; The price aspect is implemented through competitive pricing and adjustments based on fluctuations in raw material prices; The place or distribution aspect is carried out through a direct distribution system and trust between producers and distributors; The promotion aspect is carried out simply, namely through direct communication, customer testimonials, and verbal promotion. The conclusion of this study is that the marketing mix strategy consistently applied by Mbah Man White Tofu Factory is able to maintain business sustainability, increase customer loyalty, and strengthen competitiveness amid intense local market competition.